Chapter Dietary Omega-6/Omega-3 and Endocannabinoids: Implications for Brain Health and Diseases - Layé, Sophie (InTechOpen, 2016)
In this study, we compare two economic models of urban gardening in Ljubljana, Slovenia. First is an avoided costs model (ACM) and the second one is a business model (BM). Comparison is made to exemplify the main economic differences between the two models. The difference is that producers under the BM sell surplus products, which is not the case under the ACM. The main aim of this study is to present an analysis of the phenomenon of urban gardening as a BM for small family home or allotment gardens. The survey was performed through Internet questionnaires and in some cases also with on-site interviews. Totally 127 urban gardeners from Ljubljana municipality participated in the research. The average ACM urban gardeners had on 1 m2 revenue of 4.86 EUR/m2, costs of 1.48 EUR/m2 and gross margin (savings) of 3.38 EUR/m2. Altogether, ACM brings savings of approximately 462.7 EUR per average size garden (136.69 m2) or 203 EUR per median size garden (60 m2) to the average gardener. The average BM gardener sold to the wholesale company approximately 107.0 kg of vegetables per year from 32.48 m2 of production area for an average retail price of 1.46 EUR/kg and earning revenue of 156.44 EUR/year. Costs were approximately 21.27 EUR/year. Therefore, the gross margin or earning from surpluses sold was approximately 135.17 EUR/year for the average BM gardener, which was 4.29 EUR/m2 or 1.26 EUR/kg of produce. The study offers evidence that the ACM can be upgraded with the BM. For example, if a family of two retired members have an average garden of 136 m2, they can produce vegetables for four people. Consequent surpluses for two family members can be sold for extra money. The BM should be more promoted among urban gardeners as it can offer additional income and in certain cases, when a hobby becomes a profession, also a full-time job.